Use of Constant Type Cost Prorate Method in Calculation of Actuarial Liability of Pension Funds - Putrie, Veronica Clasrissa; Nurdyah, Himda Anataya (iora, 2024)
The purpose of this study is to calculate the actuarial liability value of pension funds using the Constant Percent type Cost Prorate method. This method is a pension funding method that calculates pension benefits based on the employee's salary since he first entered work. The method in this study is used to calculate the amount of actuarial liabilities that must be issued by the company to employees at the time of normal retirement, namely 58 years. The data used is the data of a Civil Servant of the Social Service in DKI Jakarta who is 55 years old. Normal contributions and actuarial liabilities that must be prepared by pension companies for pension plan participants increase as the age of pension plan participants increases. Based on the calculation results, the accumulated actuarial liabilities that must be prepared by the pension plan company in 2020 are IDR 3,843,981,410.